Pembuatan Video Profil Sebagai Media Promosi Potensi Desa Lanpasa : - - Niken Kusumarini; Nisrina Nurhaliza; Ahmad Rivaldo; Nidha Khairunnisa; Nazma Setiawati; Ahmad Ridani; Niken Aprilidiani; Akhmad Ali Mirza (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Information digitization is one of the steps that can be taken to improve public services. One example of the use of information digitization is the creation and uploading of village profiles on YouTube to introduce villages to the general public. At this time, video village profiles are essential for various purposes, such as mapping village potential, branding, and program socialization. Village governments often have difficulty creating profiles for this video, especially in Lanpasa Village. The method used in Community Service (PKM) is to use Science and Technology Substitution. Lanpasa Village is one of the villages in Seruyan Raya District, Seruyan Regency, Central Kalimantan Province. Thus, this Community Service (PKM) aims to make a profile video of Lanpasa Village. Lanpasa Village profile video, in this video describes the geographical location, economic conditions, education, and social conditions as well as the potential resources of Lanpasa Village. The creation of this profile video is expected to introduce various aspects of the village's excellence, such as natural beauty, cultural wealth, and distinctive products, to a wider audience.